The Languages of Petitioning in Early Colonial India. Issue 3 (2019) - Jaffe, James A.
Abstract : With relatively few exceptions, personal petitions from individuals have received much less attention from historians than those from groups in the public political sphere. In one sense, personal petitions adopted many of the same rhetorical strategies as those delivered by a group. However, they also offer unique insights into the quotidian relationship between the people and their rulers. This article examines surviving personal petitions to various administrators at different levels of government in western India during the decades surrounding the East India Company's conquests. The analysis of these petitions helps to refine our understanding of the place of the new judicial system in the social world of early-nineteenth-century India, especially by illuminating the discourse of justice that petitioners brought to the presentation of their cases to their new governors. The conclusion of this article seeks to place the rhetoric of personal petitioning within the larger context of mass political petitioning in India during the early nineteenth century.